Editorial - Hayes, Grahame (PINS-Psychology in Society, 2025)
Psychoanalysis. Over two years ago now (May 1988) in Psychology in society - 10 we announced our intention to devote a whole issue to psychoanalysis, psychodynamic theory and its relation to social theory and practice in South Africa. There has been much interest in our "psychoanalytic issue" over this period, although this interest has not as easily translated into print. Maybe some of the reserve in writing about psychoanalysis stems from an inherent difficulty of sustaining a psychoanalytic culture in this country. With the urgency of political and social struggles forever breathing down our necks, and now with the possibility and promise of a new South Africa before us the concerns of psychoanalysis might seem a little remote if not downright inappropriate. Psychology in society has assiduously attempted to present ideas and problems in our society in such a way that the political and the reflective moments have been dialectically embraced. Even more so now, we need to think very hard about our actions, practices and ideas. Psychoanalysis is a complex set of ideas about human experience which also needs to be thought about in its application in South Africa. It is not necessary to justify a concern with people's everyday experience in a society where the capacity of the majority to get on with their lives has been so systematically undermined. We hope that this issue of PINS stimulates some discussion and debate about the possibility of psychoanalysis and psychodynamic theory in making sense of the psychological and emotional side of people's social and political struggles.